Retrospective study on long-term effects of hormone replacement therapy (HRT) and iron chelation therapy on glucose homeostasis and insulin secretion in female ß- thalassemia major (β-TM) patients with acquired hypogonadotropic- hypogonadism (AHH) : Treatment of hypogonadal female thalassemic patients and OGTT - De Sanctis, Vincenzo; Daar, Shahina; Soliman, Ashraf; Tzoulis, Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Hypogonadism and abnormalities of glucose homeostasis, resulting from iron-induced pituitary and pancreatic β-cell dysfunction respectively, are the most frequently reported endocrine abnormalities in patients with ß-thalassemia major (β-TM), also identified as transfusion-dependent thalassemia (TDT).Study design and Patients: The aim of the present retrospective study was to evaluate the long-term effects of hormone replacement therapy (HRT) on glucose metabolism and insulin secretion/sensitivity during 3-h oral glucose tolerance test (OGTT) in adolescent and young β-TM women with acquired hypogonadototropic -hypogonadism (AHH).Twelve hypogonadal β-TM females with AHH on HRT were followed for 8.26 ± 1.49 years.Results: At baseline, 10 patients (83.3%) had normal OGTT, 1 patient presented with impaired glucose tolerance (IGT) and 1 patient had an isolated PG level of 165 mg/dL at 1-h during OGTT (H-NGT). At last evaluation, 7 patients (58.4 %) had normal OGTT, while 5 patients (41.6%) had abnormal OGTT. Reduced insulin sensitivity and impaired first-phase insulin secretion were also documented. Three of 4 β-TM patients on treatment with estradiol hemihydrate MX 50 patches plus oral medroxyprogesterone acetate (MPA), associated with a very effective iron chelation therapy, maintained normal glucose tolerance from baseline to last evaluation. Significant adverse events due to HRT or additional endocrine complications were not documented in any cases during the follow-up.Conclusion: Deterioration of glycemia (dysglycemia) occurred in 45.4% (5/11) of thalassemic females on long-term HRT. Additional studies are needed to elucidate the validity of our preliminary observations.